Chinese Herbal Medicine for Type 2 Diabetes Mellitus With Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Peng, Sihan; Liu, Lu; Xie, Ziyan; Zhang, Xiyu; Xie, Chunguang; Ye, Sha; Zhang, Xiangeng; Liang, Xiaoli; Wang, Hongyan; Liu, Ya (Frontiers in Pharmacology, 2022)
Objectives: To evaluate the efficacy and safety of Chinese herbal medicine (CHM) for type 2 diabetes mellitus(T2DM) with nonalcoholic fatty liver disease (NAFLD) with the current evidence. Methods: This study was registered in PROSPERO as CRD42021271488. A literature search was conducted in eight electronic databases from inception to Dec 2021. The primary outcomes were lipid indices and liver functions, including triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and alanine transaminase (ALT), aspartate transaminase (AST). Review Manager 5.2 and Stata v14.0 were applied for analysis. Results: The research enrolled 18 RCTs with 1,463 participants. Results showed CHM combined with western medicine (WM) was more effective than WM alone in TG (weighted mean differences(WMD)=-0.35,95% confidence interval(CI) [-0.51, -0.19], p<0.0001), TC (WMD=-0.58,95%CI [-0.80, -0.36], p <0.00001), LDL-C (WMD=-0.37, 95%CI [-0.47, -0.26], p <0.00001), HDL-C (WMD=0.20, 95%CI[0.10, 0.29], p <0.0001), ALT (WMD=-4.99, 95%CI[-6.64, -3.33], p <0.00001), AST (WMD=-4.76, 95%CI[-6.35, -3.16], p <0.00001), homeostatic model assessment of insulin resistance (WMD=-1.01, 95%CI [-1.22, -0.79], p <0.00001), fasting blood glucose (WMD=-0.87, 95%CI[-1.13, -0.61], p<0.00001), two-hour postprandial glucose (WMD=-1.45,95%CI [-2.00, -0.91], p<0.00001), body mass index (WMD=-0.73,95%CI[-1.35, -0.12], p =0.02), and overall effective rate (risk ratio (RR)=1.37,95%CI[1.29, 1.46], p <0.00001). Conclusion: The CHM in combination with WM seems to be more beneficial in T2DM with NAFLD patients in improving lipid and glucose metabolism, liver function, insulin resistance as well as improving the overall efficiency and reducing body weight. Given the poor quality of reports from these studies and uncertain evidence, these findings should be interpreted cautiously.